Efficiency of the healthcare system and the impact of smoking bans: a DEA analysis of the Guangdong-Hong Kong-Macau Greater Bay Area in Asia - Wu, Xiaoyu; Wang, Shuyang; Tang, Yulong; Wang, Jiabi; Zhang, Jinghua (Frontiers in Public Health, 2025)
ObjectiveHealthcare system efficiency is a global policy priority in the background of aging populations and in pursuit of universal health coverage (UHC). Some healthcare systems in East Asia have been recognized for being highly efficient, which is attributable to healthy lifestyles, including low smoking rates. Specifically, the Guangdong-Hong Kong-Macao Greater Bay Area (GBA) has offered a unique opportunity to study the link between smoking control and healthcare system efficiency.Materials and methodsBased on the input and output data from healthcare systems across 11 cities in the GBA between 2010 and 2019, a two-stage output-oriented Data Envelopment Analysis (DEA) was employed to assess healthcare efficiency. Additionally, Tobit regression analysis was conducted to evaluate the determinants of efficiency, including smoking rates, urbanization, population aging, and the proportion of floating populations.ResultsThere has been a general trend of improved health production efficiency over the past decade despite fluctuations caused by epidemic shocks. While significant disparities across the region have been identified, Hong Kong and Macao consistently achieved higher efficiency scores compared to other cities in the GBA. The results of the Tobit regression analysis indicate that the coefficients of smoking rates are −1.961 (p = 0.000) and −2.134 (p = 0.000), respectively, with other socioeconomic confounding factors controlled.ConclusionThe healthcare systems in the GBA highlight the critical role of smoking control measures in improving healthcare efficiency in terms of population health outcomes. These findings provide evidence-based support not only for the GBA and mainland China but also for other regions aiming to achieve UHC while addressing the health challenges of aging populations.